1996
DOI: 10.1074/jbc.271.38.23043
|View full text |Cite
|
Sign up to set email alerts
|

Elastase Release of Basic Fibroblast Growth Factor in Pulmonary Fibroblast Cultures Results in Down-regulation of Elastin Gene Transcription

Abstract: We have reported previously that a factor released by elastase treatment of pulmonary fibroblast cultures is capable of down-regulating elastin gene expression. In the present study we have pursued the identification of the factor released by elastase treatment and the characterization of the level of elastin gene expression at which this factor exerts its effect. We have found by immunologic and biochemical procedures that elastase treatment results in the release of basic fibroblast growth factor (bFGF) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 14 publications
1
67
1
Order By: Relevance
“…8,9 The mechanism most studied is probably the decreased elastin gene transcription by bFGF in human vSMCs 10 and rat pulmonary fibroblasts. [11][12][13][14] EGF and bFGF were shown to decrease elastin gene transcription by activating extracellular signalregulated kinases 1/2 (ERK1/2), resulting in its translocation to the nucleus and subsequent induction of c-fos and fra1. 10,[13][14][15] Heterodimers c-fos/c-jun and fra1/c-jun form the activator protein-1 (AP1) complex that represses elastin gene transcription through its binding to an AP1/cAMP response element-like sequence located on the human elastin gene.…”
mentioning
confidence: 99%
“…8,9 The mechanism most studied is probably the decreased elastin gene transcription by bFGF in human vSMCs 10 and rat pulmonary fibroblasts. [11][12][13][14] EGF and bFGF were shown to decrease elastin gene transcription by activating extracellular signalregulated kinases 1/2 (ERK1/2), resulting in its translocation to the nucleus and subsequent induction of c-fos and fra1. 10,[13][14][15] Heterodimers c-fos/c-jun and fra1/c-jun form the activator protein-1 (AP1) complex that represses elastin gene transcription through its binding to an AP1/cAMP response element-like sequence located on the human elastin gene.…”
mentioning
confidence: 99%
“…In the lung parenchyma, elastin deposition is thought to be a function of the septal interstitial and alveolar wall fibroblasts (26). The elastase/anti-elastase imbalance in the lung is associated with the release/induction of growth factors and cytokines (2,29), which are known to positively [transforming growth factor-␤ (TGF-␤) (22,41)] and negatively [interleukin-1␤ (IL-1␤) (1), tumor necrosis factor-␣ (TNF-␣) (12), or basic fibroblast growth factor (bFGF) (31)] modulate elastin gene expression in lung fibroblasts. Previous studies in our laboratory demonstrated that exposure of neonatal rat lung fibroblasts to neutrophil elastase (NE) and/or pancreatic elastase results in the release of biologically active epidermal growth factor receptor (EGFR) ligand(s), such as polypeptides immunochemically related to epidermal growth factor (EGF) (5) and heparinbinding EGF-like growth factor (18), leading to EGFR activation and initiation of mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinases 1 and 2 (ERK) signaling to tropoelastin mRNA downregulation (5).…”
mentioning
confidence: 99%
“…The resultant elastase digest exhibits an inhibitory activity on elastin gene expression when added exogenously to untreated fibroblasts (15). Previously, we have identified fibroblast growth factor-2 (FGF-2) as a major elastogenic inhibitory factor within the elastase digest (44). FGF-2 is a heparan sulfate proteoglycan (HSPG)-binding growth factor that is initially sequestered in the matrix of pulmonary fibroblasts.…”
mentioning
confidence: 99%